Sebuah PERJUANGAN PALESTINA DALAM PUISI ṬARĪQUN WĀHIDUN KARYA NIZAR QABBANI: (Analisis Semiotik) - Rivai, Muhammad Iqbal (Kitabina: Jurnal Bahasa dan Sastra, 2024)
This research aims to describe the description of Michael Riffaterre's semiotic analysis of the poem Ṭarīqun Wāhidun by Nizar Qabbani. The research method used is descriptive qualitative. The data and study are based on various sources, which are then analyzed using a semiotic approach and Riffaterre theory by readings heuristically and hermeneutically, the indirectness of expressions, models, variants, matrices and hypograms. The results of the analysis have been explained and presented in the form of words. The research subject is Ṭarīqun Wāhidun poetry, while the research object is the meaning or matrix in Ṭarīqun Wāhidun poetry. This researcher is based on an analysis of Riffaterre's semiotic reading which reveals the heuristic meaning of this poem is about a man who wants to get a rifle to go to the Palestinian battlefield. This research shows Nizar Qabbani's strong desire to fight for Palestine so that he was able to compose poetry very beautifully. The meaning is obtained based on a hermeneutical reading which is reinforced by the model "There is only one road to Palestine through the tip of a gun which has 4 variants, namely: gun, loss, jihad, revolutionary. The matrix of this poem is the desire to fight for Palestine by getting weapons, in which Palestine experiences the loss of its home and homeland, and invites the revolutionary to fight for jihad to liberate the land of Palestine.